Repellent effect of some plant powders in three types of stored grains beetles - Moneif Abed Mostafa (College of Education for Pure Sciences, 2009)
This study aimed to test the repellent effect powders of Solanum nigrum L., Cupressus sempervirens L., Nerium olender L., Ammi majus L., Pimpinela anisum L., Cinamomum zylanicum L., Olivera decumbence and Azadirachta excelsa Jack, at four concentrations 0.5, 1, 2 and 4 % as flour or rice grains or wheat grains treatment against the adults of Tribolium confusum L., Oryzeaphillus surinamensis L. and the third instar larvae of Trogoderma granarium Everts. Results indicated that powders of all plants showed repellent effect to the adults of O. surinamensis, except the powder of N. olender, the powder of A. majus causing high repellent to adults (- 0.952) at 4% concentration. Results showed that S. nigrum, C. zylanicum and N. olender powders had high effective repellent for T. confusum , the repellent proportion ranging between (- 0.529 to - 0.714) at 2 and 4 % concentraions. The results clearly indicated that S. nigrum was the most effective repellent (- 0.714) at 2 % concentration for the third instar larvae of T. granarium than other powders, the C. zylanicum, A. excelsa and N. olender powders were least effective repellent, while the P. anisum, A. majus, C. sempervirens and O. decumbence which attracted larvae.